In focus Eleanor Antin, Blood of a poet box, 1965-68 - Bradnock, Lucy E. (Tate, 2016)
Eleanor Antin (born 1935) is widely regarded as a pioneer in the fields of conceptual, feminist, and performance art. Blood of a Poet Box (L02859) is considered by the artist to have been her first major conceptual work. This multi-chapter project is a sustained analysis of that work. I consider the work's crucial place within Antin’s oeuvre and its relation to both traditional art and avant-garde precursors, including Marcel Duchamp, Jean Cocteau, and Joseph Cornell; its anticipation of the issues of gender, culture, and identity that would shape her later projects; and its documentation of the artistic and social networks of the American art and poetry communities in 1960s New York.